Deep rock mechanics : from research to engineering : proceedings of the International Conference on Geo-Mechanics, Geo-Energy and Geo-Resources (IC3G 2018), September 21-24, 2018, Chengdu, P.R. China /: from research to engineering : proceedings of the International Conference on Geo-Mechanics, Geo-Energy and Geo-Resources (IC3G 2018), September 21-24, 2018, Chengdu, P.R. China. (2018) - Unknown
No abstract available